Being a Mother under the COVID-19 Pandemic Lockdown: Evaluation of Perinatal Anxiety, Prenatal Attachment, and Maternal–Infant Attachment - Abbasoglu, Aslihan; Varnali, Hayriye; Tekindal, Mustafa A.; Pala, Halil G. (American Journal of Perinatology, 2022)
Objectives The novel coronavirus disease 2019 (COVID-19) pandemic has caused both physical and emotional stress throughout the population due to its worldwide impact. The unknowns about the disease, social isolation, pregnant women's concerns regarding exposure to the COVID-19, inaccessibility to necessary care, and the possibility of harm to their fetus may cause increased psychological distress during the perinatal period. We aimed to evaluate the association between perinatal anxiety, prenatal attachment, and maternal–infant attachment status among women with those who delivered their child in a tertiary-care center with rigid hospital restrictions.Study Design Term pregnant women who experienced the last trimester of their pregnancy during COVID-19 curfews between December 2020 and May 2021 were asked specifically about their concerns during the COVID-19 pandemic and they filled out the Perinatal Anxiety Screening Scale (PASS) and the Prenatal Attachment Inventory (PAI). Those who continued the follow-up within a month of period following the delivery were invited to fill out the Maternal Attachment Inventory (MAI).Results A total of 600 women completed the survey. While the evaluation of the relationship between participants' mean PAI and MAI scores showed a statistically significant positive correlation between scales (r = 0.124, p = 0.002), mean PAI and PASS scores showed a statistically significant negative correlation between scale scores (r = − 0.137, p = 0.001).Conclusion Examining the factors, affecting the attachment process of pregnant and puerperal women, will guide the improvement of the quality of health services in the COVID-19 pandemic.Key Points
Keywords: COVID-19; pandemic; prenatal attachment; perinatal anxiety; maternal attachment